Sustainability : - Farley, Heather M (Routledge, 2014)
Today, the concept of sustainability is a widespread goal that nearly everyone supports. At the same time, almost no one means the same thing when they use the term. Sustainability is so broad and overly used that it seems to mean everything to everyone. The result is that the concept has lost its meaning. In this book, the authors examine the misuses and abuses of "sustainability" and seek to refine and clarify the concept. The authors offer a new definition of sustainability – what they call neo-sustainability – to help guide policies and practices that respect the primacy of the environment, the natural limits of the environment, and the relationship between environmental, social, and economic systems.